Chemical characterization of Dichrostachys cinerea extracts using GC-MS and column chromatography - Olawale A. Akinmusire; Ayodeji A. Dahunsi; Aisha E. Dahunsi (Microbiology Independent Research Journal)
BACKGROUND: Dichrostachys cinerea , a plant known for its extensive use in traditional medicine. OBJECTIVE: D. cinerea was analyzed to identify its bioactive compounds and to assess its therapeutic potential. METHODS: Using gas chromatography – mass spectrometry (GC-MS) and column chromatography, we identified and characterized the chemical constituents of D. cinerea , shedding light on their potential health benefits. The separation and purification of a variety of compounds were performed by column chromatography, while GC-MS allowed for detailed structural analysis of these bioactive components. RESULTS: Our findings mark significant progress in the study of the chemical composition of D. cinerea , emphasizing its potential applications in pharmaceutical and medicinal fields. The identified compounds possessed useful pharmacological properties, including antioxidant, anti-inflammatory, and antimicrobial activities. Obtained data significantly advances our understanding of the plant’s bioactive properties and provides a foundation for future studies exploring its therapeutic potential. CONCLUSION: The outcomes of this study have implications for the development of novel drugs and herbal remedies, underscoring the importance of D. cinerea as a valuable resource in the quest for new medicines.